A role for BCL2L13 and autophagy in germline purifying selection of mtDNA - Kremer, Laura S.; Bozhilova, Lyuba V.; Rubalcava-Gracia, Diana; Filograna, Roberta; Upadhyay, Mamta; Koolmeister, Camilla; Chinnery, Patrick F.; Larsson, Nils-Göran (PLoS genetics, 2023)
Mammalian mitochondrial DNA (mtDNA) is inherited uniparentally through the female germline without undergoing recombination. This poses a major problem as deleterious mtDNA mutations must be eliminated to avoid a mutational meltdown over generations. At least two mechanisms that can decrease the mutation load during maternal transmission are operational: a stochastic bottleneck for mtDNA transmission from mother to child, and a directed purifying selection against transmission of deleterious mtDNA mutations. However, the molecular mechanisms controlling these processes remain unknown. In this study, we systematically tested whether decreased autophagy contributes to purifying selection by crossing the C5024T mouse model harbouring a single pathogenic heteroplasmic mutation in the tRNA Ala gene of the mtDNA with different autophagy-deficient mouse models, including knockouts of Parkin , Bcl2l13 , Ulk1 , and Ulk2 . Our study reveals a statistically robust effect of knockout of Bcl2l13 on the selection process, and weaker evidence for the effect of Ulk1 and potentially Ulk2 , while no statistically significant impact is seen for knockout of Parkin . This points at distinctive roles of these players in germline purifying selection. Overall, our approach provides a framework for investigating the roles of other important factors involved in the enigmatic process of purifying selection and guides further investigations for the role of BCL2L13 in the elimination of non-synonymous mutations in protein-coding genes.